2021
DOI: 10.1155/2021/4740924
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Chest Imaging for Surveillance of Atypical Lipomatous Tumors

Abstract: Synopsis. For ALTs, the utility of chest surveillance has not been well defined. This study suggests that chest imaging does not have a significant role in the surveillance of ALTs. Advanced local imaging and more intensive chest surveillance may be considered in cases of local recurrence. Background. Unlike other soft tissue sarcomas, atypical lipomatous tumors (ALTs) are thought to have a low propensity for metastasis. Despite this, a standard of care for pulmonary metastasis (PM) surveillance has not been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Lastly, though not specifically surveyed with routine chest imaging in this study, there were no documented lung metastases at final follow-up based on a review of medical records. This finding supports the recent findings of a study by Lazarides et al recommending against routine chest imaging in patients with an ALT [ 3 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Lastly, though not specifically surveyed with routine chest imaging in this study, there were no documented lung metastases at final follow-up based on a review of medical records. This finding supports the recent findings of a study by Lazarides et al recommending against routine chest imaging in patients with an ALT [ 3 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the proportion of patients without MDM2 results was not significantly different in the XRT and no-XRT groups, thereby theoretically lessening the impact of potential selection bias, and MDM2 status was not found to be an independent predictor of recurrence in our multivariable analysis. Other recent studies of ALT have shown histologic criteria without MDM2 testing to be an acceptable definition for patient inclusion, as Lazarides et al also demonstrated no difference in recurrence rate between MDM2 -positive tumors and those in which MDM2 FISH was not performed [ 3 ]. A final limitation of this study is the inability to account for the variability of radiation delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ALTs characterize extremity or upper trunk lesions, and WDLSs represent retroperitoneal or mediastinal lesions. ALTs/WDLSs are low-grade, malignant, adipocytic tumors that recur locally or dedifferentiate to high-grade sarcomas, but they rarely metastasize [ 6 , 7 ]. The gold standard for the diagnosis of ALTs/WDLSs is histopathological evidence of lipoblasts and lipocytes, with immunohistopathological staining positive for murine double minute 2 (MDM2) or cyclin-dependent kinase 4 (CDK4) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%